College Algebra (10th Edition)

Published by Pearson
ISBN 10: 0321979478
ISBN 13: 978-0-32197-947-6

Chapter 3 - Review Exercises - Page 269: 25



Work Step by Step

RECALL: A function's average rate of change from $x=a$ to $x=b$ is given by the formula: $\text{average rate of change} = \dfrac{f(b)-f(a)}{b-a}$ Use the formula above to obtain: $\text{average rate of change} \\= \dfrac{f(3)-f(2)}{3-2} \\=\dfrac{(2-5\cdot 3)-(2-5 \cdot 2)}{1} \\=\dfrac{(2-15)-(2-10)}{1} \\=\dfrac{-13-(-8)}{1} \\=\dfrac{-13+8}{1} \\=\dfrac{-5}{1} \\=-5$ Thus, the average rate of change of the given function from $x=2$ to $x=3$ is $-5$.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.